Formaldehyde traces and quality characteristics of indian mackerel (rastrelliger kanagurta) from markets in kota bharu - Hari Haraprien A/L K. Kesavan (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 5436 – Research Project Formaldehyde is a naturally occurring organic compound found to be present in fish, yet higher traces formaldehyde has significant effect on health of the consumers and quality characteristics. This study is conducted to analyse the formaldehyde traces and quality characteristics in Indian Mackerel (Rastrelliger kanagurta) in Malaysia. A total of six Indian Mackerel samples was randomly collected from Siti Khadijah Wet Market and AEON Mall Supermarket located in Kota Bharu, Kelantan. Formaldehyde was extracted from the fish samples using Trichloroacetic acid followed by the Gas Chromatography – Mass Spectrometry (GC-MS) method for qualitative analysis of formaldehyde traces. There were no traces of formaldehyde present in all six Indian Mackerel samples. The quality characteristics of the Indian Mackerel was assessed using the sensory quality assessment and pH to determine the differences in fish qualities obtained from Siti Khadijah Wet Market and AEON Mall Supermarket. Sensory quality was assessed based on characteristics such as odour, appearance and texture of the Indian Mackerel along with the pH. The result analysis has shown that Siti Khadijah Wet Market has higher degree of fish quality compared to AEON Mall Supermarket. The amount of formaldehyde obtained was compared with at most 5 ppm which is regulated by The Food Act 1983 and The Food Regulations 1985 of Malaysia. Surprisingly, this study recorded no formaldehyde in purchased Indian Mackerel in either wet market or supermarket indicating it is safe for human consumption. Keywords: Indian Mackerel, Formaldehyde, Quality Characteristics, GC-MS, Human Consumption, Kota Bharu